1993
DOI: 10.1128/jb.175.20.6546-6552.1993
|View full text |Cite
|
Sign up to set email alerts
|

Functional exchangeability of the ABC proteins of the periplasmic binding protein-dependent transport systems Ugp and Mal of Escherichia coli

Abstract: The periplasmic binding protein-dependent transport systems Ugp and Mal of Escherichia coli transport sn-glycerol-3-phosphate and maltose, respectively. The UgpC and MalK proteins of these transport systems, which couple energy to the transport process by ATP-hydrolysis, are highly homologous, suggesting that they might be functionally exchangeable. Complementation experiments showed that UgpC expression could restore growth of a malK mutant on maltose as a carbon source, provided that it was expressed at a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 47 publications
3
60
0
Order By: Relevance
“…This observation indicated that HisP and MalK share domains that are exchangeable, whereas other domains confer system specificity by providing for interactions between the membrane-spanning protein and the ATP-binding protein (12,17). Furthermore, complete ATP-binding proteins have successfully been exchanged between the Mal and Ugp transporters, which in E. coli transport maltose and sn-glycerol-3-phosphate, respectively (5). The N-terminal parts of the UgpC and MalK proteins exhibit approximately 60% sequence identity, which is much higher than the 35.6% sequence identity over the first 150 amino acids between the TauB and SsuB proteins.…”
Section: Discussionmentioning
confidence: 88%
“…This observation indicated that HisP and MalK share domains that are exchangeable, whereas other domains confer system specificity by providing for interactions between the membrane-spanning protein and the ATP-binding protein (12,17). Furthermore, complete ATP-binding proteins have successfully been exchanged between the Mal and Ugp transporters, which in E. coli transport maltose and sn-glycerol-3-phosphate, respectively (5). The N-terminal parts of the UgpC and MalK proteins exhibit approximately 60% sequence identity, which is much higher than the 35.6% sequence identity over the first 150 amino acids between the TauB and SsuB proteins.…”
Section: Discussionmentioning
confidence: 88%
“…UgpB is a specific binding protein, and ugpA and ugpE are membrane-imbedded proteins. UgpC is an ATP-binding protein that has a strong homology with the functionally exchangeable protein (MalK) for maltose transport (21). UgpQ is a glycerol phosphoryl phosphodiesterase that only hydrolyzes the assimilated diesters at the inner surface of the cytoplasmic membrane, and thus is not required for glycerol phosphate transport (20).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to mutants with point mutations in fhuB, which are albomycin resistant and fail to transport ferrichrome (25), derivatives that are impaired in the uptake of the different iron (III) hydroxamates to various extents were isolated. It is unlikely that FhuC recognizes ferric hydroxamates, since it has been demonstrated that the FhuC equivalent MalK of maltose transport complements a UgpC mutant of sn-glycerol-3-phosphate transport and vice versa (18), excluding substrate specificity of these energy-providing proteins. In this paper, it is shown that FhuD to a large extent contributes to the substrate specificity of transport through the cytoplasmic membrane.…”
Section: Discussionmentioning
confidence: 99%